Determination Method of the ATP, ADP, and CTP Concentrations by Electrochemical Reduction of Benzoquinone. Issue 15 (24th October 2019) - Xu, Wenwen; Sun, Yonghong; Shao, Cuimin; Wang, Jianguo
Abstract : ATP, ADP, and cytidine triphosphate (CTP) are common sources of energy for various cellular activities. Therefore, a method that efficiently measures ATP, ADP, and CTP levels is urgently needed. In unbuffered solution, ATP, ADP, and CTP were observed to cause a new cathodic peak at a positive potential during benzoquinone (BQ) reduction. The hydrolysis of ATP, ADP, and CTP generated additional proton donors, which provided numerous protons for the reduction of BQ and formation of a large new cathodic peak. The peak current difference between the peaks caused by ATP, ADP, and CTP before and after hydrolysis was linear to the ATP, ADP, and CTP concentrations but independent of the BQ concentration. An electrochemical method for the detection of ATP, ADP, and CTP was developed using a bare glassy carbon electrode. The proposed method showed good selectivity for the detection of ATP samples.